The stability of titania-silica interface - Staykov, Aleksandar; Ferreira-Neto, Elias Paiva; Cruz, Jean Mina Ybarrena Santa; Ullah, Sajjad [UNESP]; Rodrigues-Filho, Ubirajara Pereira (My University, 2018)
Silica is very often the catalyst support of choice for transition metal oxides such as titania, and specially anatase. Titania is an excellent absorber and photocatalyst for many organic molecules degradation. In order to understand the chemical nature of the interaction between titania and silica, we have performed a theoretical study using density functional theory aiming to elucidate the role on the stability of the interface of the specific type of interactions, H-bonding, covalent bonding of the pristine surfaces, and covalent bonding after silicon and titanium ions interdiffusion. The calculations were carried out for hydrogen and oxygen terminated surface, comparing the bonding types and the forces acting along the interface. The interface dynamics was studied for interfaces under applied stress in order to elucidate their stability and failure limits. The shearing forces and the mechanisms of interface failure were determined. Interfaces with interdiffused Si and Ti ions were studied to improve the interface stabilization. The results demonstrate that high-temperature treatment leading to formation of SiOTi bonds at the interface is responsible for the formation of strong and flexible binding interaction between both oxides. At high strains, the SiOTi interface failure is observed due to lattice mismatch between the SiO2 and TiO2. The failure is a result of forces acting orthogonal to the interface shearing. In case of hydrogen terminated surface, the interface binding is a result of hydrogen bond network. Such interface is fragile at moderate shearing forces along the applied strain. The hydrogen bond network decreases the elastic properties and flexibility of the interface. The SiO2/TiO2 interface is further stabilized by Si/Ti ion interdiffusion. The ionic interdiffusion process also increases the interface flexibility. Thus, in order to obtain more stable anatase photocatalyst supported on silica, the synthetic routes should favor silicon and titanium ions interdiffusion along the interface.
Keywords: density functional theory; interface; silica; titania